Modeling studies of acoustic propagation through the Agulhas Current region - Courtney, Jennifer Susan (Department of Oceanography, 2016)
The motivation for this thesis arises from the apparent global warming problem. It is common knowledge that the ocean is an important heat sink and that to predict global warming trends it is important to measure changes in the ocean temperature. Measurements of ocean temperature are subject to large local variability associated with mesoscale features. In order to measure global warming trends a method is required to determine large scale averages, over large oceanic ranges, in order to remove the inherent variability associated with mesoscale features, such as currents and mesoscale eddies. This requirement can be met by acoustic thermometry.